PHYTOCHEMICAL, FLUORESCENCE AND ANTIMICROBIAL EVALUATION OF POLY HERBAL EXTRACT - Rizwana Manzoor (International Journal of Pharmacy & Integrated Health Sciences, 2021)
Background and Objectives: Natural products and traditional medicines are of great importance. Such forms of medicine as traditional Chinese medicine, Ayurveda, Kampo, traditional Korean medicine, and Unani havebeen practiced in some areas of the world and have blossomed into orderly-regulated systems of medicine. Allium sativum L., crude drug (Liliaceae) used as herbal medicine to treat hyperglycemia, cancer, cardiovascular disease, hypertension, stress and infections. Malus domestica B., fruit (Rosaceae) possess antioxidant, antiproliferative, antimicrobial and anti-inflammatory activity and used for the treatment and prevention of asthma, diabetes and hyperlipidemia. Capsicum annum L., crude drug (Solanaceae) is used as anti-diabetic, anti cancer, anti-inflammatory, analgesic, hypolipidemic, hepatoprotective and antimicrobial agent. Foeniculum vulgare M., crude drug (Apiaceae) is used as antioxidant, antimicrobial, bronchodilatory, estrogenic, diuretic, hepatoprotective, gastroprotective and hypotensive agent. Curcuma longa L., crude drug (Zingiberaceae) is used various biological actions including anti-inflammatory, antioxidant, analgesic, antifertility, antidiabetic, anticoagulant, antiulcer and antimicrobial.